(untitled) (Journal of University of Babylon for Engineering Sciences, 2020)
Renewable energy is the most important type of energy sources nowadays. It’s clean, abundantly available and can be obtained from nature without giving any negative impact to the environment. This is the opposite of what fossil fuel does by giving the carbon dioxide (CO2) emission and makes a huge damage to the atmosphere. Solar energy is one type of renewable energy and is considered a good effective alternative source of energy. The solar energy can be collected using solar panels from emitted radiation from the sun. The aim of this paper is building a dual-axis solar tracker to control the direction of the panels and get the highest output efficiency compared to the fixed panels. The sun tracker system consists of two main parts, hardware, and software. Hardware represented by using a microcontroller, Light Dependent Resistors (LDRs) to detect the light of the sun, servomotors use to adjust the direction of the solar panel (PV). The software represented by the application used and the codes. The results show that the dual axis tracking is more powerful than the fixed position solar cells and achieves better output power. The power measured were obtained by the data logger method.